The elimination of Madagascar's vanilla marketing board, ten years on - Cadot, Olivier 1982- (Policy research working paper, 2006)
"This paper explores how the elimination of Madagascar's Marketing Board in 1995 affected prices paid to farmers, incentives, and regional indicators of poverty and inequality. After steadily losing market share, Madagascar has been able to regain some of the lost ground since the mid-1990s. Margins between freight on board (FOB) and farmgate prices have spectacularly narrowed down, but this effect is dwarfed by that of world-price volatility. A counterfactual analysis based on a model of Cournot competition between vanilla traders suggests that whatever limited competition there is among them has contributed to raise purchase prices and the cash income of vanilla farmers. But the effect on farmers' consumption remains small because a large part of it is self-consumed. The effect on aggregate measures of poverty and inequality is even smaller, even at the regional level. After taking into account the reduction in Madagascar's monopoly power on the world vanilla market implied by the elimination of the Marketing Board, the induced rise in producer prices is estimated to have lifted about 20,000 individuals out of poverty. "--World Bank web site